A study of Open Access research data repositories developed by BRICS countries. Issue 1 (20th November 2020) - Misgar, Safat Mushtaq; Bhat, Ajra; Wani, Zahid Ashraf
Abstract : Purpose: In the present era, research data is a concern for researchers, as they are trying to find new ways to communicate their research findings and conclusions to other researchers in order to increase visibility and credibility. BRICS nations are fast emerging economies and contribute significantly in research output. This study makes an effort to analyze and explore the role of BRICS nations towards open access research data repository registered with Registry of Research Data Repositories. Design/methodology/approach: The data were gathered from re3data repository, and the search was limited to BRICS nations. The data were further analyzed and tabulated as per set parameters, namely, country-wise distribution, types of contents, subject coverage and language diversity. Findings: The findings depict that in terms of strength, India has the highest number of data repositories, thereby achieved the first rank among BRICS nations, and South Africa has the least number of data repositories, whereas in terms of content type and subject coverage, India again is leading among BRICS nations. The English language is used by repositories as the main language of the interface. Practical implications: The study helps to understand the development of research data repositories by BRICS nations. The study is further beneficial to researchers, as Registry of Research Data Repository provides a single platform to access repositories from various disciplines. Readily available data saves time, money and efforts of researchers and helps the researcher in completing their research activity in a very short span of time. Originality/value: The paper has investigated open access data repositories of BRICS nation that has not been attempted earlier. This gives readers comprehensive overview of research data repositories developed in fast emerging economies of the global. The paper can be very helpful for information managers, OA promoters and education and research policy makers to devise plans and policy bearing in mind the evolving research channels in emerging economies.